Factors Important in the Extraction, Stability and in Vitro Assembly of the Hepatitis B Surface Antigen Derived from Recombinant Plant Systems - Smith, Mark L.; Keegan, Mark E.; Mason, Hugh S.; Shuler, Michael L. (Biotechnology progress, 2002)
The expression of vaccine antigens in edible plant material together with their delivery by the oral route constitutes a powerful paradigm, with the potential to dramatically reduce the cost of vaccine production and administration, in addition to improving distribution and patient compliance. These products will be subject to many of the same regulations applied to current injectable vaccines, so reliable methods to quantify antigen and ensure stability in crude plant extracts are required. As a model system the hepatitis B surface antigen (HBsAg) was expressed in soybean and tobacco cell cultures. This complex antigen consists of membrane‐associated small surface antigen proteins (p24s), disulfide cross‐linked to yield dimers and higher multimers. Although the total p24s extracted from plant cells was relatively unaffected by detergent concentration, the quantification of antigenically reactive product depended strongly on the ratio of detergent to cell concentration. Furthermore, 1–20% w/v sodium ascorbate improved the measured levels of monoclonal‐reactive antigen 4‐ to 12‐fold. Detergent also influenced antigen stability in cell lysates stored at 4 °C; under optimum conditions stability was maintained for at least 1 month, whereas excess detergent rendered the antigen susceptible to proteolytic degradation. This proteolysis could be counteracted by the addition of skim milk or its protein component, which stabilized antigenically reactive p24s for up to 2 months. The immunologically relevant epitopes of HBsAg are critically dependent on disulfide bonding. By altering the sodium ascorbate concentration or buffer pH the proportion of HBsAg displaying the monoclonal reactive epitopes was increased between 8‐ and 20‐fold. In addition, under certain conditions the dimerized p24s could be converted to oligomeric aggregates, resembling the form of the serum‐derived antigen. These simple in vitro manipulations, compatible with the goal of a minimally processed oral vaccine, may prove valuable in increasing the immunogenicity of the plant‐derived antigen.